Is Social Ontology Prior to Social Scientific Methodology?. Issue 3 (June 2019) - Lauer, Richard
In this article, I examine "Ontology Matters!" (OM!) arguments. OM! arguments conclude that ontology can contribute to empirical success in social science. First, I capture the common form between different OM! arguments. Second, I describe quantifier variance as discussed in metaontology. Third, I apply quantifier variance to the common form of OM! arguments. I then present two ways in which ontology is prior to social science methodology, one realist and one pragmatic. I argue that a pragmatic interpretation of ontology's priority gives proponents of realist OM! arguments a special burden that they must meet to render their argument successful.